2017
DOI: 10.1002/ptr.5802
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness ofAgeratina pichinchensisExtract in Patients with Vulvovaginal Candidiasis. A Randomized, Double-Blind, and Controlled Pilot Study

Abstract: Previous clinical studies have demonstrated the antifungal effectiveness of Ageratina pichinchensis extracts when topically administered to patients with dermatomycosis. The objective of this study was to evaluate the effectiveness and tolerability of a 7% standardized extract of A. pichinchensis (intravaginal) in patients with vulvovaginal candidiasis. The extract was standardized in terms of its encecalin content and administered during 6 days to patients with Candida albicans-associated vulvovaginitis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Several compounds have been isolated from this species, but others have been obtained by acetylation, hydrogenation, ozonolysis, iodination, or epoxidation of some of these compounds [ 16 , 42 , 44 ]. The biologically most prominent compounds are encecalinol ( 11 ), encecalin ( 12 ), encecanescin ( 17 ), 3,5-diprenyl-4-hydroxyacetophenone ( 21 ), 7- O -( β -D-glucopyranosyl)-gossypetin ( 30 ), and 7- O -( β -D-glucopyranosyl)-galactin ( 31 ), which have mainly antifungal, antiulcer, wound healing, and some antibacterial and anti-inflammatory activities [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several compounds have been isolated from this species, but others have been obtained by acetylation, hydrogenation, ozonolysis, iodination, or epoxidation of some of these compounds [ 16 , 42 , 44 ]. The biologically most prominent compounds are encecalinol ( 11 ), encecalin ( 12 ), encecanescin ( 17 ), 3,5-diprenyl-4-hydroxyacetophenone ( 21 ), 7- O -( β -D-glucopyranosyl)-gossypetin ( 30 ), and 7- O -( β -D-glucopyranosyl)-galactin ( 31 ), which have mainly antifungal, antiulcer, wound healing, and some antibacterial and anti-inflammatory activities [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another case, a clinical study was carried out on vaginal suppositories made with 7% HEA-7:3 containing approximately 15 mg of Compound 12 in female patients diagnosed with vulvovaginal candidiasis. Application of suppositories for 6 days revealed a therapeutic efficacy of 81.2%, while the control of clotrimazole (100 mg) was 86.6%; the tolerability was 94.1% for patients treated with the extract and 93.7% for those treated with clotrimazole [ 19 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, unpigmented hexane-ethyl acetate extract at 5% was evaluated over 11 days in patients with stomatitis, showing that A. pichinchensis reduces the size of buccal lesions and pain scores, with an effectivity of 100% at the end of the study [ 199 ]. Clinical uses of this folk plant have been extended to onychomycosis, vulvovaginal candidiasis [ 200 ], diabetic foot ulcers [ 201 ] and tinea pedis [ 202 ]. Despite several clinical studies, there is only one preclinical study about the antinociceptive and anti-neuropathic properties of this plant.…”
Section: Preclinical Studies Of Mexican Medicinal Plants Used In Inflammatory and Neuropathic Pain Treatmentmentioning
confidence: 99%
“…King and H. Rob. is a plant with ethnopharmacological relevance in Mexico, and its several pharmacological activities have been confirmed in murine models and clinical trials in vivo , such as onychomycosis ( Romero-Cerecero et al, 2009 ), interdigital tinea pedis ( Romero-Cerecero et al, 2012b ), stomatitis ( Romero-Cerecero et al, 2015b ), and vulvovaginal candidiasis ( Romero-Cerecero et al, 2017 ). Despite its use for wound healing, the first study showed that the daily topical application of an aqueous extract from the aerial parts of A. pichinchensis heals wounds in rats without inducing skin irritation ( Romero-Cerecero et al, 2011 ).…”
Section: Plants From Asteraceae Family As Wound-healing Agentsmentioning
confidence: 99%